Peculiarities of Game Modes Effect on Dynamics of Speed Development in Boys of Primary School Age - С. І. Марченко; В. О. Голубов (OVS LLC, 2015)
Research objective: to experimentally verify the effectiveness of use of game modes systemized for development of speed abilities in boys of primary school age. Research methods: 1.Theoretical analysis and collation of scientific and methodological literature. 2. Method of control tests. 3. Pedagogical experiment. 4. Methods of mathematical statistics. Research results. Positive changes in the level of speed abilities development occurred both in the reference and test groups with better performance in the test groups. This effect resulted from the rational planning of game load. The study has established that to develop speed, the second-fourth grade boys are to engage in five games. The number of repetitions for the second-third graders is one, the rest intervals being 40 seconds, and the number of repetitions for the fourth grade boys is two, rest intervals being 30-40 seconds. The most effective development manifests during the 20-30 lessons. Favorable for speed development are games and relays performed with the highest speed from the start and at short distances from 10 to 30 m.